1996
DOI: 10.1002/(sici)1096-9861(19960408)367:3<454::aid-cne10>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution of neurotrophin receptors in the developing auditory brainstem

Abstract: Neuron survival and axonal regeneration become severely limited during early postnatal development. In conjunction with our recent organotypic analysis of regeneration in the auditory midbrain, we wished to determine whether neurotrophins could serve as a trophic substance during the postnatal period. Therefore, the current study examines the development of three neurotrophin receptor tyrosine kinases (TrkA, TrkB, and TrkC) in the gerbil auditory brainstem. Immunoreactivity to TrkA, the nerve growth-factor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Although neurotrophins and their receptors are essential to the survival of peripheral auditory neurons (Ernfors et al, 1995), little is known about their role in developing central auditory pathways. Hafidi et al (1996) have shown recently that TrkB and TrkC receptors are localized at postsynaptic sites on central auditory neurons and that TrkB receptors develop in parallel with auditory function in the brainstem auditory system of the gerbil. These authors suggest that brain-derived neurotrophic factor and neurotrophin-3, the ligands for TrkB and TrkC receptors, respectively, may be regulated by neuronal activity in the auditory pathway and may act as survival signals for auditory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although neurotrophins and their receptors are essential to the survival of peripheral auditory neurons (Ernfors et al, 1995), little is known about their role in developing central auditory pathways. Hafidi et al (1996) have shown recently that TrkB and TrkC receptors are localized at postsynaptic sites on central auditory neurons and that TrkB receptors develop in parallel with auditory function in the brainstem auditory system of the gerbil. These authors suggest that brain-derived neurotrophic factor and neurotrophin-3, the ligands for TrkB and TrkC receptors, respectively, may be regulated by neuronal activity in the auditory pathway and may act as survival signals for auditory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that GABAergic transmission could play a significant role during inhibitory synaptogenesis. Second, MNTB neurons express neurotrophins, and LSO neurons express their cognate receptors during development (Hafidi 1999;Hafidi et al 1996). Since neurotrophin/Trk signaling pathways have been shown to modulate synaptic transmission (Kang and Schuman 1995;Kim et al 1994;Levine et al 1998), they may be relevant to the plasticity displayed by MNTB synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, L-VGCC-mediated signaling has been tightly linked to BDNF expression (87)(88)(89). However, BDNF (69) and its major receptor TrkB (70) are barely expressed at P0 throughout the auditory brainstem, and their expression increases up to P15, implying a role during the maturation of auditory neurons. Similar results have been obtained for NTF3, NTF4, and TrkC (70,69).…”
Section: Discussionmentioning
confidence: 99%
“…TrkA is not expressed at all (70). In contrast, p75NTR is expressed already in the perinatal auditory brainstem and present even at late embryonic stages (71).…”
Section: Analyses Of Candidate Pathways For Increased Postnatalmentioning
confidence: 99%